1983
DOI: 10.1136/jcp.36.4.392
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological systems of breast cancer classification: reproducibility and clinical significance.

Abstract: SUMMARY The inter-and intraobserver reproducibilities of the histopathological systems of breast cancer classification suggested by the World Health Organisation (WHO), the Armed Forces Institute of Pathology (AFIP) and Ackerman have been analysed. The reproducibilities of the three classification systems were only "fair" to "moderate" and no correlation with the five-year recurrence rate was found. Our results indicate that these classification systems are without biological significance and are useless for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…In our study the overall interobserver agreement regarding the diagnoses of TMC, AMC, and NMC in the first and second evaluation is 72% and 68%, respectively, corresponding to Kappa values of 0.55 and 0.52, which are both moderate according to Landis & Koch [17]. Stenkvist et al [21] have examined the interobserver reproducibilities of the histopathological systems of breast cancer classification suggested by WHO, AFIP, and Ackerman, and they found the best reproducibility in the WHO system with an equal assessment of 76% and a Kappa of 0.49, which again according to Landis & Koch is moderate and thus equates with the reproducibilities in our study. Another study of observer variability in the reporting of breast lesions has been performed by Swanson Beck et al [22], who used a simplified six point classsification system that covered the range from normal tissue to invasive carcinoma.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In our study the overall interobserver agreement regarding the diagnoses of TMC, AMC, and NMC in the first and second evaluation is 72% and 68%, respectively, corresponding to Kappa values of 0.55 and 0.52, which are both moderate according to Landis & Koch [17]. Stenkvist et al [21] have examined the interobserver reproducibilities of the histopathological systems of breast cancer classification suggested by WHO, AFIP, and Ackerman, and they found the best reproducibility in the WHO system with an equal assessment of 76% and a Kappa of 0.49, which again according to Landis & Koch is moderate and thus equates with the reproducibilities in our study. Another study of observer variability in the reporting of breast lesions has been performed by Swanson Beck et al [22], who used a simplified six point classsification system that covered the range from normal tissue to invasive carcinoma.…”
Section: Discussionmentioning
confidence: 94%
“…In the study by Stenkvist et al [21] the intraobserver variation in the WHO system of pathologists i and 2 was 76% and 69%, respectively, with corresponding Kappa values of 0.49 and 0.38, which can be interpreted as 'moderate' and 'fair'. In the study by Swanson Beck et al the average intraobserver agreement was 78%.…”
Section: Discussionmentioning
confidence: 97%
“…The comparison of these results with those from other institutions is difficult to determine. It is well known that there is a wide variation of results from different institutions (Stenkvist et al, 1983;Gilchrist et al, 1985). In his review, Clayton (1991) found the proportion of well-differentiated tumours to be between 3% and 33% and the proportion of poorly differentiated tumours to be between 25% and 67%.…”
Section: Discussionmentioning
confidence: 99%
“…Rationale for an unweighted combined scoring of these three correlated variables has never been put forth, but a relationship between grade of invasive ductal carcinoma (IDC) of the breast and outcome has been recognized consistently. 3,4,[7][8][9] Strength of the prognostic relationship has fallen short of levels necessary for critical therapeutic decisions, and reproducibility of grading has remained a matter of concern [10][11][12][13][14][15][16][17][18][19] (Table 1). The Cooperative Breast Cancer Tissue Resource (CBCTR) has collected and categorized 9000 breast cancer specimens available as formalin-fixed blocks in paraffin.…”
mentioning
confidence: 99%